Three Decades of Green Finance: The State of the Art and Way Forward - Miyan, Md. Sazib; Cheong, Calvin W. H.; Sharif, Arshian; Afshan, Sahar (International Journal of Energy Economics and Policy, 2024)
Green finance (GF) constitutes a multifaceted research domain, yet extant reviews often provide fragmented insights from subsets rather than a holistic examination of the entire green finance corpus. To bridge this gap, this study endeavors to conduct an extensive review to offer a comprehensive overview of green finance’s performance and intellectual landscape. Leveraging a dataset of 2685 articles from the Scopus database spanning 1991-2023, this study aims to unveil influential articles, top contributing journals, authors, institutions, and countries in green finance research. Additionally, it elucidates seven principal thematic clusters in GF research, encompassing responsible investment, carbon and climate financing, green banking and economy, green finance and innovation, sustainability, environmental finance, and sustainable finance. Furthermore, this study outlines six prospective avenues for future GF research, including the integration of behavioral finance principles, the utilization of modern technologies, and the formulation of policy frameworks to enhance sustainability and curb greenwashing practices aimed at advancing sustainable practices and addressing emerging challenges.